Analysis of Raw Material Inventory Control with A Tabular Approach and Formula Approach Economic Order Quantity (EOQ) to Optimize The Cost of Soybean Raw Material Inventory At The Rizqy Putra Fried Tofu Factory - Winarti Shofariah; Faldy Herdian (Jurnal Indonesia Sosial Sains, 2024)
Inventory management is a crucial aspect in the operations of the manufacturing industry, including in fried tofu factories such as the Rizqy Putra Fried Tofu Factory. The main raw material, namely soybeans, must be managed efficiently to ensure smooth production and minimize the costs incurred. This research aims to determine the inventory control of soybean raw materials applied by Rizqy Putra Fried Tofu Factory, the total inventory cost, and the optimal quantity of soybean raw material orders. This research is quantitative research with a comparative descriptive analysis. The data processed are the inventory purchase and usage reports of soybean raw materials at Rizqy Putra Fried Tofu Factory in 2023. The data analysis method used in this research includes two approaches: the tabular approach and the formula approach with the calculation technique of Economic Order Quantity (EOQ). Based on the results of the research, the inventory control method applied by Rizqy Putra Fried Tofu Factory is the traditional or conventional method, where the total inventory cost of soybean raw materials is Rp. 18,720,000 with details of storage costs amounting to Rp. 18,000,000 and ordering costs of Rp. 720,000 per year, and an ordering frequency of 48 times with an average order quantity of 5,875 kg. Meanwhile, according to the calculation of the formula approach EOQ, the optimal order quantity is 2,880 kg, with an ordering frequency of 24 times and the total inventory cost incurred is Rp. 734,387. The conclusion of this research indicates that based on the calculation of the EOQ formula approach, the total inventory cost of soybean raw materials is more optimal compared to the conventional method applied by Rizqy Putra Fried Tofu Factory.